2021
DOI: 10.3389/fonc.2021.637823
|View full text |Cite
|
Sign up to set email alerts
|

Are All Anti-Angiogenic Drugs the Same in the Treatment of Second-Line Metastatic Colorectal Cancer? Expert Opinion on Clinical Practice

Abstract: Targeting tumor-driven angiogenesis is an effective strategy in the management of metastatic colorectal cancer (mCRC); however, the choice of second-line therapy is complicated by the availability of several drugs, the occurrence of resistance and the lack of validated prognostic and predictive biomarkers. This review examines the use of angiogenesis-targeted therapies for the second-line management of mCRC patients. Mechanisms of resistance and anti-placental growth factor agents are discussed, and the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 124 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…In addition to inhibiting the VEGF/VEGFR pathway, TKI drugs may also inhibit targets related to immune regulation, such as platelet-derived growth factor receptor (PDGFR), angiopoietin-2 receptor (TIE2), and colony-stimulating factor 1 receptor, and have stronger synergy with immunotherapy. [92][93][94] EGFR EGFR is a member of the epidermal growth factor receptor (HER) family, which includes HER1 (erbB1, EGFR), HER2 (erbB2, NEU), HER3 (erbB3), and HER4 (erbB4). 95,96 Studies have shown that EGFR is overexpressed or abnormally expressed in many solid tumors.…”
Section: Vegf/vegfrmentioning
confidence: 99%
“…In addition to inhibiting the VEGF/VEGFR pathway, TKI drugs may also inhibit targets related to immune regulation, such as platelet-derived growth factor receptor (PDGFR), angiopoietin-2 receptor (TIE2), and colony-stimulating factor 1 receptor, and have stronger synergy with immunotherapy. [92][93][94] EGFR EGFR is a member of the epidermal growth factor receptor (HER) family, which includes HER1 (erbB1, EGFR), HER2 (erbB2, NEU), HER3 (erbB3), and HER4 (erbB4). 95,96 Studies have shown that EGFR is overexpressed or abnormally expressed in many solid tumors.…”
Section: Vegf/vegfrmentioning
confidence: 99%
“…Generally, anti-angiogenic and anti-kinase agents are combinatorically administrated with fluoropyrimidine-based chemotherapy plus OXP and/or IRI ( 189 , 190 ). Among these, the following are clinically approved and used in mCRC treatment regimens: bevacizumab (VEGF inhibitor), aflibercept (blocks activation of VEGF-A, VEGF-B, and PIGF), ramucirumab (anti-VEGFR-2 monoclonal antibody), and regorafenib ( 191 ) with approval and reimburse differently applied in the countries. This last one is a multikinase inhibitor that not only acts on angiogenic protein kinases (VEGFR-1, VEGFR-2, VEGFR-3, TIE-2), but as well on proteins involved in oncogenesis (KIT, RET, RAF-1, BRAF, BRAF V600 ), metastasis (PDGFR, FGFR), and tumor immunity (CSF1R) ( 192 , 193 ).…”
Section: Liquid Biopsy In Colorectal Malignanciesmentioning
confidence: 99%
“…These factors induce tumors to acquire more angiogenic and invasive potentials, promoting metastasis [ 144 ] . Preclinical studies and clinical trials suggest that inhibition of a specific growth factor can induce the expression of others [ 145 ] . For instance, in a phase II study in which mCRC patients were treated with a combination of 5-FU, leucovorin and irinotecan (FOLFIRI) and bevacizumab, several angiogenic factors, including the placental growth factor and hepatocyte growth factor, were found to increase before disease progression [ 146 ] .…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%